1991
DOI: 10.1002/elan.1140030307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proteins on the response of anion‐selective electrodes based on vitamin B12 derivatives

Abstract: KmtWky 40506-0055, U.S.A. ABSTRACTThe potentiometric response of several polymer membrane based ion-selective electrodes prepared with hydrophobic vitamin B,, derivatives is described. The effect of different proteins on the properties of these electrodes is discussed. It is suggested that the observed changes in potential upon addition of proteins are due mainly to nonspecific interactions between the proteins and the polymer membrane. Reduction of the nonspecific binding effect is possible by using a polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The study also investigated the activity of trypsin by following the decrease in the EMF response to the polycationic protein protamine, as it is cleaved into smaller fragments by the enzyme. Protein binding as a function of ionophore concentration in the membrane for ISEs prepared with hydrophobic vitamin B 12 derivatives was also investigated 9. The study showed that non‐specific protein adsorption was lower when the amount of hydrophobic B 12 ionophore was reduced in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The study also investigated the activity of trypsin by following the decrease in the EMF response to the polycationic protein protamine, as it is cleaved into smaller fragments by the enzyme. Protein binding as a function of ionophore concentration in the membrane for ISEs prepared with hydrophobic vitamin B 12 derivatives was also investigated 9. The study showed that non‐specific protein adsorption was lower when the amount of hydrophobic B 12 ionophore was reduced in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…This loss in detection limit is most likely the result of nonspecific binding of the protein to the hydrophobic PVC surface. According to a mechanism described previously [31,33,34], this protein adsorption creates a ™blocked interface∫ through which ions must diffuse in addition to the normal diffusion layer resulting in an increased impedance of the membrane surface to the phase transfer of chloride ions [31,34]. The potential changes observed at low chloride concentration are then limited due to this layer.…”
Section: Mc3-based Ises For Blood Measurementsmentioning
confidence: 97%
“…There is clearly a difference between the slopes and detection limits of PVC and PVC/VAGH membranes. The decrease in these parameters for VAGH membranes most likely results from the more hydrophilic nature of this polymer, which influences either the extraction of chloride into the membrane, the strength of ionionophore interaction, ionophore conformation and solubility, or all of these parameters [33,35]. When the sample solution was changed to include HEPES, the difference in slope À 45 AE 1 mV/decade) and detection limit 9 AE 2 mM) for chloride from calibrations in water are less pronounced probably due to the poorer interaction of the more hydrophilic polymer with the sulfonate functionality of the HEPES anion.…”
Section: Mc3-based Ises For Blood Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…The proposed mechanisms for the selective anion-carrying ability of metallomacrocycles in membranes usually involve the exchange of the axial ligand by the anion of interest (17)(18)(19). The axial-ligand exchange properties derive from the nature of the coordination between the metal ion and the ligand, and can be influenced by changing either the metal center or some of the ring constituents (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Therefore, by manipulating the structure of the complexes, it should be possible to control the selectivity characteristics of the ionophores.…”
Section: Potentiometric Sensors Based On Electropolymerized Porphyrinsmentioning
confidence: 99%